How to Communicate Effectively with Anyone, Anywhere : Your Passport to Connecting Globally - Sanchez, Raúl, 1977-; Bullock, Dan, 1983- (Career Press, 2021)
"In our increasingly interconnected world, communication is key. Whether speaking in public, writing an email, or going through an important negotiation, how you present yourself through your language is all important in today's global business world. This book reveals a new approach to global communication across key performance areas, including effective emailing, public speaking, and negotiation. Readers will gain not only the practical skills essential for operating across cultural settings but also a firm foundation for managing transactions of global business, international relationships, and worldwide innovation"--